Negotiating power in Ezra-Nehemiah - Laird, Donna (Atlanta : SBL Press, 2016)
"Donna Laird examines Ezra and Nehemiah in the light of modern sociological theorist Pierre Bourdieu. How did this context of hardship, exile, and return change what Ezra and Nehemiah viewed as important? How did they define who was a part of their community, and who was an outsider? It goes on to explore how the books engaged readers at the time: how it addressed their changing circumstances, and how different groups gained and used "social power," or the ability to influence society"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; Bible; RELIGION / Biblical Studies / Exegesis & Hermeneutics; RELIGION / Biblical Studies / Old Testament; Criticism, interpretation, etc; Electronic books